efektivitas aplikasi katakana memory hint terhadap penguasaan katakana siswa sma - suryana syarif; Nova Yulia (Universitas Negeri Padang, 2021)
This study discusses the katakana mastery of grade X students in SMAN 4 Pariaman. The aim of this study was to find out the katakana mastery of grade X students in SMAN 4 Pariaman. This research is quantitative research which the samples were the students of X IPA 3 consisting of 25 students for each class. The data in this study are done by using the grade X students' scores of the katakana test results. Based on the results of data analysis in this research, it can be concluded that the katakana mastery of grade X students in SMAN 4 Pariaman after using Katakana Memory Hint application is categorized in good qualifications with 81.76 as the average score. Meanwhile their mastery of katakana before using Katakana Memory Hint application is in more than sufficient qualifications with 61,92 as the average score. Based on the results of hypothesis testing, it is concluded that there is a significant effectiveness and use of Katakana Memory Hint application on katakana mastery of grade X students of SMAN 4 Pariaman because of the value of thitung>ttabel (6,08>1,68).